Genesis and development of the teaching's paradigm during the republican period: the Normal School for Teachers and Teachers of East - Daineris Mancebo-Céspedes; Julia Esther Céspedes-Acuña (Maestro y Sociedad, 2018)
During the republican stage, it was an I claim of intellectuals and educators the creation of a school institution that guarantees the stability in the formation of the men and women that would exercise the task of teaching in the public schools of the country. He/she didn't go until the promulgation of the law that in 1915 this missed dream would see its reality, with the foundation in each capital of county of a normal school. The objective of the present article, is to explain the beginnings and development of the Normal School for Teachers and Teachers of East, which knew how to guarantee the quality in the impartation of the decencies, due to the presence of a cloister of a vast culture as well as to the heap of extracurricular activities that you/they were carried out that transformed it into reference center in the city of Santiago from Cuba without doubts.